Родинний вроджений адреногенітальний синдром - Бирюкова, М. С.; Хижняк, О. О.; Любимова, Л. П.; Бондаренко, В. О.; Кравчун, Н. О.; Андрєєв, І. І. (Clinical Endocrinology and Endocrine Surgery, 2008)
A case from clinical practice of congenital adrenogenital syndrome is presented. To two children from one family (sister and brother from passports data) after birth was diagnosed adrenogenital syndrome, and in 19 years at one of them was diagnosed combination of adrenogenital syndrome with gonadal dysgenesis. The patients are inspected and treated in the clinic of Institute of problems of endocrine pathology during 13 years.